Improved receiver tracking models for scintillation monitoring - Susi, Melania (2017)
Strong ionospheric electron content gradients may lead to fast and unpredictable fluctuations in the phase and amplitude of the signals from Global Navigation Satellite Systems (GNSS). This phenomenon, known as scintillation, can impair the tracking performance of a GNSS receiver, leading to increased phase and Doppler errors, cycle slips and sometimes to complete losses of signal lock. In order to mitigate scintillation effects at receiver level, the robustness of the carrier tracking loop, the receiver’s weakest link under scintillation, must be enhanced. Thanks to their adaptive nature, Kalman Filter (KF) based tracking algorithms are particularly suitable to cope with the variable working conditions imposed by scintillation. However, the effectiveness of this tracking approach strongly depends on the accuracy of the assumed dynamic model, which can quickly become inaccurate under randomly variable scenarios. This research work shows how inaccurate dynamic models can lead to a KF suboptimum solution or divergence when both strong phase and amplitude scintillation are present. Then, to overcome this issue, two novel self-tuning KF based carrier tracking algorithms are proposed. They self-tune their dynamic models by exploiting the knowledge about scintillation, which is achieved by estimating a number of scintillation indices. These types of tracking schemes are particularly suitable for ionospheric scintillation monitor receivers, which are designed for the computation of scintillation indices and other related parameters. Moreover, this thesis analyses and implements algorithms for a reliable computation of scintillation indices even when low cost receivers are exploited. Furthermore, a technique is proposed to compute scintillation indices even if temporary losses of signal lock or cycle slips occur. All algorithms have been assessed by exploiting both simulated and real data affected by high latitude and equatorial scintillation. Results show that the proposed algorithms are able to maintain the signal lock and provide reliable scintillation indices when classical architectures and commercial Ionospheric Scintillation Monitoring Receivers (ISMRs) fail.